Distinct Worst Pain Profiles in Oncology Outpatients Undergoing Chemotherapy. Issue 3 (10th May 2023) - Shin, Joosun; Oppegaard, Kate; Calvo-Schimmel, Alejandra; Harris, Carolyn; Cooper, Bruce A.; Paul, Steven M.; Conley, Yvette P.; Hammer, Marilyn J.; Cartwright, Frances; Kober, Kord M.; Levine, Jon D.; Miaskowski, Christine
Abstract : Background: While pain is a significant problem for oncology patients, little is known about interindividual variability in pain characteristics. Objective: The aims of this study were to identify subgroups of patients with distinct worst pain severity profiles and evaluate for differences among these subgroups in demographic, clinical, and pain characteristics and stress and symptom scores. Methods: Patients (n = 934) completed questionnaires 6 times over 2 chemotherapy cycles. Worst pain intensity was assessed using a 0- to 10-point numeric rating scale. Brief Pain Inventory was used to assess various pain characteristics. Latent profile analysis was used to identify subgroups of patients with distinct pain profiles. Results: Three worst pain profiles were identified (low [17.5%], moderate [39.9%], severe [42.6%]). Compared with the other 2 classes, severe class was more likely to be single and unemployed and had a lower annual household income, a higher body mass index, a higher level of comorbidity, and a poorer functional status. Severe class was more likely to have both cancer and noncancer pain, a higher number of pain locations, higher frequency and duration of pain, worse pain quality scores, and higher pain interference scores. Compared with the other 2 classes, severe class reported lower satisfaction with pain management and higher global, disease-specific, and cumulative life stress, as well as higher anxiety, depression, fatigue, sleep disturbance, and cognitive dysfunction scores. Conclusions: Unrelieved pain is a significant problem for more than 80% of outpatients. Implications for Practice: Clinicians need to perform comprehensive pain assessments; prescribe pharmacologic and nonpharmacologic interventions; and initiate referrals for pain management and psychological services.